Enhancing Elementary Students' Dance Movement Skills Through Doratoon Media Based on Local Cultural Arts - Hidayatillah, Yetti; Jamilah; Misbahudholam AR, Muhammad (Jurnal Edutech Undiksha, 2024)
Teachers' lack of understanding regarding the concept and purpose of dance education affects the design of learning programs, which tend to be monotonous and less creative. This condition impacts students' dance movement skills in elementary schools. This study aims to examine the effectiveness of Doratoon media based on local cultural arts in improving students' dance movement skills. The research employed a quantitative method with a pre-experimental design of the one-group pretest-posttest type, where one group was tested before and after using the learning media. The research instrument was a dance movement skills test administered to students. The data were analyzed using hypothesis testing through a t-test. The results showed that the use of Doratoon media based on local culture was highly effective in improving students' dance movement skills, as evidenced by the tvalue being higher than the ttable (9.42 > 2.262). Moreover, the developed dance skills video media has the potential to be published through YouTube as an effort to expand learning access and improve dance skills more actively and creatively. The conclusion of this study is that Doratoon media can be effectively used as an alternative local culture-based learning tool to enhance students' dance movement skills in elementary schools.